A Review of Herbal Therapy in Multiple Sclerosis - Sina Mojaverrostami; Maryam Nazm Bojnordi; Maryam Ghasemi-Kasman; Mohammad Ali Ebrahimzadeh; Hatef Ghasemi Hamidabadi (Tabriz University of Medical Sciences, 2018)
Multiple sclerosis is a complex autoimmune disorder which characterized by demyelination and axonal loss in the central nervous system (CNS). Several evidences indicate that some new drugs and stem cell therapy have opened a new horizon for multiple sclerosis treatment, but current therapies are partially effective or not safe in the long term. Recently, herbal therapies represent a promising therapeutic approach for multiple sclerosis disease. Here, we consider the potential benefits of some herbal compounds on different aspects of multiple sclerosis disease. The medicinal plants and their derivatives; Ginkgo biloba, Zingiber officinale, Curcuma longa, Hypericum perforatum, Valeriana officinalis, Vaccinium macrocarpon, Nigella sativa,Piper methysticum, Crocus sativus, Panax ginseng, Boswellia papyrifera, Vitis vinifera, Gastrodia elata, Camellia sinensis, Oenothera biennis, MS14 and Cannabis sativa have been informed to have several therapeutic effects in MS patients.